2003
DOI: 10.1029/2002jc001321
|View full text |Cite
|
Sign up to set email alerts
|

Observations of oceanic whitecaps in the north polar waters of the Atlantic

Abstract: [1] Digital photographs of the sea surface were analyzed for the fraction of aerial coverage by whitecaps (stage A and B) in the north polar region of the Atlantic. Photography was accompanied by measurements of wind velocity, air temperature and humidity, sea surface temperature, and observations of significant wave height. Whitecap coverage increased significantly with an increase in wind speed (or wind friction velocity). Our data exhibit lower values of the average whitecap coverage at low and moderate win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 45 publications
7
135
1
Order By: Relevance
“…10) is negative and, following the usual interpretation, yields a threshold wind speed of about 1.1 m s −1 for whitecap inception. This is in the range of previously published values from 0.6 (Reising et al, 2002) to 6.33 (Stramska and Petelski, 2003). Meanwhile, the positive y intercept b for W 37 (Eq.…”
Section: Wind Speed Dependencesupporting
confidence: 74%
“…10) is negative and, following the usual interpretation, yields a threshold wind speed of about 1.1 m s −1 for whitecap inception. This is in the range of previously published values from 0.6 (Reising et al, 2002) to 6.33 (Stramska and Petelski, 2003). Meanwhile, the positive y intercept b for W 37 (Eq.…”
Section: Wind Speed Dependencesupporting
confidence: 74%
“…Recent studies indicated that the whitecap coverage is influenced by the state of the wind wave development. It has been shown that the larger whitecap coverage, the more developed wind waves at the same wind speed (Stramska and Petelski, 2003;Lafon et al, 2004;Sugihara et al, 2007;Callaghan et al, 2008;Goddijn-Murphy et al, 2011), while the existence of swell appears to suppress the whitecap coverage (Sugihara et al 2007;Goddijn-Murphy et al, 2011). Based on comprehensive observational data, Zhao and Toba (2001) found that whitecap coverage is better correlated with the windÁsea Reynolds number R B than the wind speed alone, and they proposed a quasi-linear relationship:…”
Section: Model Of Gas-transfer Velocity In the Presence Of Wave Breakingmentioning
confidence: 99%
“…Slower sampling rates and lower resolutions were used during HiWASE, since the cameras were serviced only every two or three months rather than every day. A grayscale image analysis similar to that employed by Stramska and Petelski (2003) was used to isolate whitecaps from the surrounding sea. Initial results show an increase of whitecap fraction with wind speed (Fig.…”
Section: Wave Breaking and Whitecap Measurements Whitecap Coverage Ementioning
confidence: 99%